Dystonia: A Leading Neurological Movement Disorder - Kabir, Md. Tanvir; Yasmin, Hasina; Khanam, Umme Salma; Jamiruddin, Mohd. Raeed; Uddin, Md. Sahab; Abdel-Daim, Mohamed M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Dystonia is the third leading movement disorder arising mainly from the damage of basal ganglia or other parts of the brain that control movements. The objective of this review is to represent the detailed profile of dystonia. A computerized literature review was conducted in authentic scientific databases including PubMed, Google Scholar, Scopus, Science Direct and National Institutes of Health (NIH) etc. Terms searched included dystonia, risk factors, etiologies, clinical features, classification, pathology, guidelines, treatment strategies, primary and secondary dystonia. Initially, 97 articles and 9 books were extracted but finally, 64 articles and 7 books were used. After analysis, we found that causes of dystonia could be acquired or inherited and dystonia can be classified based on age at onset, etiology, and distribution of the affected body parts. The risk factors of this heterogeneous disorder could be trauma, thyroid disorder, hypertension, life habits, occupation, use of drugs and genetics. A significant number of articles were found which signify the ability of brainstem and cerebellar pathology to trigger the symptoms of dystonia. Since antipsychotic drugs are the most commonly prescribed among the people with intellectual disability (ID), therefore they possess a greater risk to experience antipsychotic drugs-induced movement side effects including acute dystonia, parkinsonism, tardive dyskinesia, and akathisia. Depending on various manifestations and causes, there are several treatment options including oral medications, intramuscular injection of botulinum toxin, neurosurgical procedures and occupational therapy.